KAJIAN PENGGUNAAN LAHAN TRADISIONAL MINANGKABAU BERDASARKAN KONDISI TANAHNYA - Nandi Kosmaryandi (Department of Forest Resources Conservation and Ecotourism - IPB University, 2005)
Minangkabau society contends the land not only for living-sources but also as symbol of social status and origin. Land is common ownership following the community social hierarchy. There are directions based on customs for the use of the land. The adage about it is “nan rato kaparumahan, tabu tumbuah dinan lereng, kok manggu kapakuburan, nan bancah ditanam sawah”. This adage was the result of adapting to environmental conditions in highland areas, as well as erodeble condition.Key words: tradition, Minangkabau, erodeble